Educational courses on non-pharmacologic complementary interventions for nurses across Europe: The INES mapping pilot study. (September 2022) - van der Heijden, Marianne J.E.; Busch, Martine; Gunnarsdottir, Thora Jenny; Lunde, Anita; Falkenberg, Torkel; van Dijk, Monique
Abstract: Background: Pharmacological interventions still form the mainstay of the management of pain, anxiety, sleep problems and discomfort. In Europe, an estimated 100 million people use complementary non-pharmacological interventions (NPIs) for these conditions. In their pre-registration education, nurses do not generally learn about the various types of NPIs and how patients and health care professionals can include NPIs complementary to their standard care. Some nursing schools in Europe offer elective courses on NPIs, often relying on individual initiatives. Little is publicly available about the content of these programmes and how they relate to the current nursing curriculum for EU countries. Objectives: This pilot study aims to explore and map the field of nursing education with regard to complementary NPIs for nurses in Europe. Design: A web-based open-access questionnaire administered through the online survey tool LimeSurvey® was designed by the authors. Participants: The questionnaire was sent to a purposive sample of 49 experts on nurse education and complementary NPIs from 16 European countries. All levels of education were eligible for inclusion. Methods: The questionnaire consisted of 35 items regarding course content, teaching material, teaching methods and methods of assessment. In addition, respondents were invited to perform a strengths, weaknesses, opportunities and threats (SWOT) analysis in relation to their education programme. Qualitative data was analyzed using a directive content analysis approach. Results: Between January and May 2020, thirty-one completed questionnaires from ten different countries were returned (response rate 63.3%). Massage, meditation, mindfulness and relaxation are the most taught interventions. Anxiety, stress, chronic pain, depression and sleep problems are the most common symptoms addressed. Conclusions: Currently, a consistent and European approach to education for nurses on complementary NPIs and integrative nursing is lacking. Although taught at regular nursing educational institutes, the courses discussed here are not yet embedded in mainstream education for nurses.